Mobilising the indigenous practice of making Oshikundu using an inquiry-based approach to support Grade 8 Life Science teachers in mediating learning of enzymes - Shinana, Ester Ndakondja Lineekela (Rhodes University, Faculty of Education, Department of Education, 2020)
The Namibian curriculum encourages Life Science teachers to integrate indigenous knowledge into their science lessons. Additionally, it also encourages teachers to promote scientific inquiry in their science classrooms. However, it is not clear how Life Science teachers should go about doing this. As a result, science is taught in decontextualised ways and inquiry-based methods are neglected. It is against this background that this study sought to mobilise the indigenous practice of making oshikundu to mediate learning of enzymes and to promote inquiry-based methods. Essentially, an attempt was made to mediate the learning of enzymes through inquiry-based methods using, in particular, the Predict-Explain-Explore-Observe-Explain (PEEOE)approach.The approach entails learners making predictions and providing explanations for their predictions before they do their observations. The study employed a qualitative case study approach underpinned by an interpretive paradigm. It was conducted at two schools in the Omusati Region in Namibia and three Life Science teachers (two from one school and one from a different school) participated in this study.A variety of data gathering techniques such as document analysis, workshop discussions, participatory observation, and journal reflections were used to gather data and for triangulation purposes. A thematic approach to data analysis was adopted and data analysis and interpretation we redone inductively using Vygotsky's socio-cultural theory and Shulman's Pedagogical Content Kno Knowledge (TSPCK) model was used as the analytical framework to identify and improve the quality of Life Science teachers' PCK in the topic of enzyme s in particular. Findings from this study revealed that some teachers had a narrow understanding of the concept of scientific inquiry, whereas some demonstrated a better understanding of the concept and how it is used in Life Science classrooms. The findings also revealed that the understanding of the teachers of an inquiry approach and how they understood science should be taught, further influenced their practice ; this was in addition to resource constraints. Furthermore, it was also established that some teachers did not include the concept of enzymes in their teaching. The workshop intervention equipped teachers with the knowledge on an inquiry approach and how to promote scientific inquiry skills in their classrooms. Likewise, the practical demonstration of making oshikundu also equipped the teachers with the knowledge of enzymes and together with the PEEOE approach, how to teach enzyme s using an inquiry approach. Teachers experienced challenges, as they had to use their creative, critical thinking and reasoning skills in order to identify the scientific concepts from the practical demonstration of oshikundu. The study suggests that there is a need for professional development programmes focusing specifically on supporting in-service science teachers' understanding of inquiry and how to use the inquiry-based approach in their classrooms. Equally, the pre-service science teachers need such preparations during their training. Furthermore, the study also presents that there is a need to engage both pre-service and in-service teachers deeply with the new content of the Life Science syllabus.
Keywords: Education, Secondary -- Namibia; Ethnoscience -- Namibia; Fermented beverages -- Namibia; Science -- Study and teaching (Secondary) -- Namibia; Enzymes -- Study and teaching (Secondary) -- Namibia; Ethnoscience -- Study and teaching (Secondary) -- Namibia